2017
DOI: 10.1007/s12603-016-0777-z
|View full text |Cite
|
Sign up to set email alerts
|

Joint association of obesity and hypertension with disability in the elderly—A community-based study of residents in Shanghai, China

Abstract: Low or extremely high BMI, independent of its metabolic consequences, is a risk factor for disability among the elderly. Simple hypertension wasn't significantly associated with disability. In addition, having hypertension significantly increased the risk of ADL disability in obese individuals and IADL disability in underweight individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Although hypertension is one of the most important preventable contributors to disease and death [30], several studies also show different result when focusing on the relationship between hypertension and disability [11,12,31,32]. For example, Uddin et al found hypertension was signi cantly associated with lower ADL scores in Bangladesh [31]; our previous study indicated that simple hypertension wasn't signi cantly associated with ADL/IADL disability [24]. In present study, we found only poor hypertension control was associated with ADL/IADL disability, while hypertension control was not.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although hypertension is one of the most important preventable contributors to disease and death [30], several studies also show different result when focusing on the relationship between hypertension and disability [11,12,31,32]. For example, Uddin et al found hypertension was signi cantly associated with lower ADL scores in Bangladesh [31]; our previous study indicated that simple hypertension wasn't signi cantly associated with ADL/IADL disability [24]. In present study, we found only poor hypertension control was associated with ADL/IADL disability, while hypertension control was not.…”
Section: Discussionmentioning
confidence: 99%
“…About 50% eligible participants from this street o ce were randomly targeted through use of a local household registry. Details of inclusion criteria, data collection and quality control procedure have been previously reported [24,25]. In brief, 9408 community-dwelling residents, who aged 60 years or older and had living in Shanghai for more than 5 years, were screened.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations